ANALISIS KELAS KATA VERBA BAHASA DAERAH TIDORE DI DESA TADUPI KECAMATAN OBA TENGAH KOTA TIDORE KEPULAUAN - Amarullah, Nurfabila; Muharam, Rijal (FKIP Universitas Khairun, 2025)
This study aims to describe the form and function of verb word classes in the Tidore regional language used by the people of Tadupi Village, Oba Tengah District, Tidore Islands City. Using a descriptive qualitative method with a structural linguistic approach, data were obtained through observation, interviews, and documentation of native Tidore speakers who still actively use the language in daily interactions. The results of the study show that verbs in Tidore play a role as the center of predication in sentences and express the meaning of actions, states, and events. From the data collection, 81 verb forms were found, including routine activity verbs, physical action verbs, and verbs that express states or emotions. Morphologically, most verbs undergo an affixation process, especially through the use of the prefix ma- which marks active actions and so- which indicates ongoing aspects. The syntactic structure of verbs functions to connect subjects with objects or adverbs, while also marking modality and aspects of actions according to the context of use.